Screening for retinopathy of prematurity – qualification criteria on the basis of our experience - Hautz, Wojciech; Grałek, Mirosława; Dobrzańska, Anna; Trzebicka, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Retinopathy of prematurity is a serious disease which may cause blindness. Modern laser treatment is effective but must be done in right time. The aim of the work is to answer the question: what principles should be used in ophthalmic screening in Poland. 267 premature newborn with 3rd stage of ROP treated with laser coagulation were taken into account. Birth weight of treated children ranged from 490 to 1980 grams, gestation age ranged from 23 to 34 weeks. Laser photocoagulation was carried out between 25 and 147 days of life. Analysis of the above data leads to the following conclusions: compulsory screening for ROP in Poland should be limited to all children born before or in 34 week of gestation and children with birth weight less than 2000 grams; first examination should take place in the 4th week of life.